Effect of Feeding Coated Sodium Butyrate on Growth Performance and Forage Digestibility in Suckling Buffalo Calves (Indian Journal of Animal Production and Management, 2024)
Feeding trial of 105 days was conducted in neonatal buffalo calves (n=24) to assess the effect of  coated sodium butyrate in inducing early rumen development activity and general performance. The  included three experimental groups, Control group receiving normal calf starter, Treatment group fed  500 ppm coated sodium butyrate in the calf starter and Treatment fed 1000 ppm coated sodium  butyrate in the calf starter. The sex ratio of each treatment group was maintained 50:50. Parameters  recorded during the trial include voluntary intake of calf starter and body weight changes and rumen  development in terms of forage digestibility was assessed at the end of the trial. Results indicate that  addition of 1000 ppm coated sodium butyrate improved palatability of calf starter, weight gain,  roughage intake and digestibility. The investigators recommend supplementation of coated sodium  butyrate in the calf starter for better growth performance.
Keywords: Coated sodium butyrate; digestibility; growth; suckling buffalo calves